Theological reflection, assurance and the doctrine of God - Masango, Maake J. (HTS teologiese studies, 2019)
This article focuses on the anxiety about whether God loves one or not. In the author’s nearly 30-year ministry, this pastoral difficulty continues to perplex and afflict. While the presenting problem is what in theological parlance is ‘a lack of assurance’, a side difficulty is the poor and incorrect doctrine of God often associated with this. A Baylor University Study in 2006 characterises the kind of God that different groups of Americans believe in. While the phrase ‘a lack of assurance’ is a part of dogmatic parlance, and has fallen out of use, the feeling of not belonging to God can be overwhelming for people. This feeling may be overwhelming. This makes it a pastoral issue. This article suggests a pastoral response to this issue and a proposal for a clarification in the nature and character of God using the therapeutic theology of 19th-century Scottish minister-theologian John McLeod Campbell.